2019
DOI: 10.1101/544122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MDiNE: A model to estimate differential co-occurrence networks in microbiome studies

Abstract: Motivation:The human microbiota is the collection of microorganisms colonizing the human body, and plays an integral part in human health. A growing trend in microbiome analysis is to construct a network to estimate the co-occurrence patterns among taxa though precision matrices. Existing methods do not facilitate investigation into how these networks change with respect to covariates. Results:We propose a new model called Microbiome Differential Network Estimation (MDiNE) to estimate network changes with resp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Mandakovic and colleagues compared microbial co-occurrence networks representing bacterial soil communities from different environments to determine the impact of a shift in environmental variables on the community’s taxonomic composition and their relationships [ 22 ]. MDiNE is another recently developed model for estimating differential co-occurrence networks in microbiome studies [ 23 ]. Notably, Faust et al [ 24 ] applied generalized boosted linear models to infer thousands of significant co-occurrence and co-exclusion relationships between 197 clades occurring throughout the human microbiomes; their study revealed reverse correlation between functional similarity and phylogenetic distance among bacterial species, which is unsurprising.…”
Section: Introductionmentioning
confidence: 99%
“…Mandakovic and colleagues compared microbial co-occurrence networks representing bacterial soil communities from different environments to determine the impact of a shift in environmental variables on the community’s taxonomic composition and their relationships [ 22 ]. MDiNE is another recently developed model for estimating differential co-occurrence networks in microbiome studies [ 23 ]. Notably, Faust et al [ 24 ] applied generalized boosted linear models to infer thousands of significant co-occurrence and co-exclusion relationships between 197 clades occurring throughout the human microbiomes; their study revealed reverse correlation between functional similarity and phylogenetic distance among bacterial species, which is unsurprising.…”
Section: Introductionmentioning
confidence: 99%
“…Subtle perturbation and co-occurrence patterns. Microbes with co-occurrence patterns were known to be driven by metabolic interactions and competition for resources 26 , and had the potential to capture crucial community characteristics that might not be discovered in microbial diversity or abundance-based analysis 27,28 . Based on 25 highly correlated microbial families ( r C i B i ) with peculiar co-occurrence (ascent, descent, and convex) abundance patterns ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several approaches have been proposed to address co-occurrence networks including the Spearman correlation analysis used by Gupta et al 4,5 and suggested by ours colleagues Fu et al 1 These methods usually deal with a number of taxa (OTUs) large relative to the sample size and assume sparsity (an abundance of 0 entries) to achieve stable precision matrix estimation. 7 However, inadequate (small) sample sizes remain a major drawback, resulting in unstable estimates of precision matrices for which applying a penalization scheme is recommended as we and other authors previously reported. 7 Even when using Lasso as an efficient solution in the domain of sparse precision matrix estimation, having a limited sample size (<30 samples) tends to produce unstable co-occurrence data and networks to our knowledge.…”
Section: To the Editormentioning
confidence: 88%
“…7 However, inadequate (small) sample sizes remain a major drawback, resulting in unstable estimates of precision matrices for which applying a penalization scheme is recommended as we and other authors previously reported. 7 Even when using Lasso as an efficient solution in the domain of sparse precision matrix estimation, having a limited sample size (<30 samples) tends to produce unstable co-occurrence data and networks to our knowledge.…”
Section: To the Editormentioning
confidence: 88%